2001
DOI: 10.1177/0146167201271006
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Contextual Constraints and Chronic Expectancies on Behavior Categorizations and Dispositional Inferences

Abstract: The authors examined the roles of chronic expectancies and other contextual information in the dispositional inference process within the domain of ability judgments. Prior to viewing a vid- Whenextractinginformationaboutothers'enduringdispositions from their behavior, perceivers may have access to a vast array of contextual cues, including prior information about the target, situational information, and event-outcome information. Perceivers also have at their disposal knowledge structures, such as schemas and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Pilot testing for an earlier study (Weary, Reich, & Tobin, in press) demonstrated that this manipulation results in negative expectancies ( M s = 4.81 and 5.69 on 9-point scales of performance and intellectual expectancies, respectively, compared with 7.35 and 6.85 for a positive expectancy condition, p s < .001) comparable to those that result from the manipulation of distinct negative expectancies (see Footnote 8).…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…Pilot testing for an earlier study (Weary, Reich, & Tobin, in press) demonstrated that this manipulation results in negative expectancies ( M s = 4.81 and 5.69 on 9-point scales of performance and intellectual expectancies, respectively, compared with 7.35 and 6.85 for a positive expectancy condition, p s < .001) comparable to those that result from the manipulation of distinct negative expectancies (see Footnote 8).…”
Section: Methodsmentioning
confidence: 77%
“…The other participants were given instructions designed to suggest that the level of the target's general performance had been unsuccessful. This procedure has been used in two other studies (Weary, Reich, & Tobin, in press) to create negative expectancies that are, by definition, not separable from the actual performance information. The theoretical rationale underlying the predictions for the current Studies 1 and 2 suggests that such nondistinct expectancies would be used as interpretation frames and would result in assimilation of perceivers' relatively automatic behavior categorizations and target characterizations to them.…”
Section: Studymentioning
confidence: 99%
“…In fact, it is expected that if teachers are not provided with sufficient time to reflect on their assessment and evaluation of students or of their work, they may be prone to ignore situational constraints in their judgment of students (cf. Chun et al 2002;Tetlock, 1985;Weary et al 2001). In a similar vein, stress or cognitive load can contribute to an increased ignorance of contextual factors (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly enough, given the chance to reflect on their choices in the debriefing following the questionnaire, some of the participants report the tendency to minimize unnecessary jumps to dispositional conclusions through self-imposed self-reflection (cf. Weary et al 2001). The debriefing phase also addressed the importance of fair and inclusive diagnostic processes in (foreign language education) and drew on the direct experience from everyday school life (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation